FAKTOR-FAKTOR KESULITAN BELAJAR STATISTIK MAHASISWA STAI KI AGENG PEKALONGAN - Gunawan, Muhammad Ali; Fitri, Amalia (Universitas Pekalongan, 2024)
Statistics is an important subject for students in many different branches of study, including STAI Ki Ageng Pekalongan. However, many students have trouble studying statistics. This study seeks to determine the factors that contribute to problems in studying statistics at STAI Ki Ageng Pekalongan. This study employs a descriptive method combined with a quantitative approach. Data was acquired through a poll of 21 STAI Ki Ageng Pekalongan students attending statistics courses. Data were examined via descriptive statistics. The findings of this study reveal that various factors cause difficulty in studying statistics at STAI Ki Ageng Pekalongan, including 1) lack of comprehension of basic mathematical ideas, 2) difficulties comprehending statistical formulae, and calculations, 3) lack of practice with statistical issues, and 4) poor drive to learn.